Discurso de ódio e atividade parlamentar: uma leitura sobre dimensões do poder, democracia e ilicitude - Cortez, Marcelo André Antunes de Souza (2022)
Inserted in the Social Relations and Dimensions of Power Research Line, this dissertation aims to debate how the progressive growth of hate speech (Hate Speech) in parliamentary activity can be understood as a political strategy for weakening and destroying democracy in the Brazil, throughout the first two decades of the 21st century. To understand this phenomenon, the research makes a brief historical analysis of the formulation of State liberalism, developed by several classic and contemporary theorists. Under the justification of defending freedom of expression, hate speeches reflect the permissiveness and distortion of the democratic foundations of the State, promoted by the bankruptcy of the neoliberal capitalist system, providing a consequent rise of far-right movements with populist and fascist languages ​​in Brazil , tensioning social relations and the dimensions of power. The research uses the concept of performative language to understand how discourses from the new Brazilian right are widely used by parliamentarians as instruments that aim to undermine the foundations of the Democratic Rule of Law.